Neo-aesthetic theory complexity and complicity must be defended - Šuvaković, Miško 1954- (Hollitzer, 2017)
A permanent state of emergency: a neo-aesthetic view on contemporary politics and art Miško Šuvaković describes his experience of the twentieth and twenty-first centuries as a "permanent state of emergency". The author explores this perspective in relation to the politics of time (dialectic historicizing) and the politics of space (geographic difference). By mapping visual arts, performance arts, architecture, music, new media and postmedia arts with contemporary theory, philosophy and aesthetics, he challenges established conceptualizations in modern and contemporary art movements.